On the Cauchy Problem for Degenerate Difference Equations of the mth Order in a Banach Space - Semenyshyna, I. V.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish sufficient conditions for the solvability of the Cauchy problem for degenerate difference equations of the mth order in a Banach space.